PERFORMA PRODUKSI IKAN NILA (Oreochromis niloticus) PADA PEMELIHARAAN SISTEM BIOFLOK DENGAN JENIS BAKTERI PROBIOTIK KONVENSIONAL YANG BERBEDA - Sesa Safitrah Liana; Andre Rachmat Scabra; Muhammad Sumsanto (Jurnal Perikanan Unram, 2024)
They are fish(Oreochromis niloticus) is one of the freshwater fish that is easy to keep, its growth is relatively fast. Apart from that, it is a consumer favorite because of its thick flesh and delicious taste. One technology that can be used as an alternative is biofloc technology because it is able to minimize land use and improve water quality and increase nutrient utilization. Probiotics containing microorganisms can be given via feed or water as a medium. Supraptoet al., (2013), expressed the opinion that the use of probiotics in the environment for bioremediation can improve water quality and break down organic matter. This research aims to evaluate the performance of tilapia production in a biofloc system with different types of conventional probiotics. This research used an experimental method with the experiment used was a Completely Randomized Design (CRD) starting from 5 treatments repeated 3 times. The provision of probiotics in the water media of the biofloc system has a significant effect on the parameters of absolute weight growth, absolute length growth, and floc volume. With each treatment, the best was obtained in treatment B, namely 9.51 grams, treatment C was 0.15ml/l. Meanwhile, the addition of probiotics to the biofloc system water media had no effect on the parameters of erythrocytes, leukocytes, hematocrit, hemoglobin.